Pengenalan dan Pemanfaatan Ikan Tembakul (Boleophthalmus pectinirostris) sebagai Bahan Baku Pembuatan Nugget dalam Upaya Pemenuhan Gizi Masyarakat Pesisir di Masa Pandemi Covid-19 - Tri Adi Wibowo; Desy Sasri Untari; Rohmatul Anwar; Novita Novita (Universitas Sriwijaya, 2021)
Pandemic Covid-19 require for the implementation of restrictions on social interaction and outdoor activities. A decrease in the activity if it lasts a long time will have an impact on the decline in the income of the community. This is an effect of the purchasing power of the basic needs as well as the fulfillment of nutrition. While the conditions of the pandemic requires the fulfillment of nutrition, especially protein as a nutrient in maintaining the durability of the body. Mudskipper (Boleophthalmus pectinirostris) can be a cheap source of protein and easily obtainable by the people who live in the coastal region. This study aims to introduce the coastal communities in the Village Sriminosari, East Lampung Regency against potential mudskipper as a source of protein that are easily obtained during a pandemic without having to conduct operations from the sea, and strategies to increase its economic value with processed into fish nuggets. Research methods include field survey, observation or direct observation, discussion and interviews using research instruments in the form of questionnaires. Respondents were selected using the method of withdrawal of random samples of simple (simple random sampling). Testing of raw materials mudskipper using sheets of organoleptic test raw material in accordance with SNI 2729-2013. Test sensory processed nuggets using sheet test sensory tools reference SNI 2346:2015. The results of the research show the value of organoleptic mudskipper as a raw material that is 7,59 ? µ ? 7,73, and the value of the test sensory mudskipper nugget amounted to about 7.42? ? ? 7,74. This study provides knowledge to the community that mudskipper can be utilized in the fulfillment of nutrition, especially protein, answer the public stigma that mudskipper non-toxic and can be consumed as well as pose a public initiative to develop nuggets but by utilizing the raw material of other types of fish are abundant in the current season, but have no economic value in terms of price.